The Effectiveness Of The Ite Law In Handling Hate Speaking Through Social Media In Batam City - Elan; Situmeang Ampuan; Junimart Girsang (IHSA Institute, 2022)
The results of this study explain that the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions is a form of embodiment of the responsibility that must be carried out by the State, to provide maximum protection for all activities using technology. information and communication to be well protected from potential crime and misuse of technology. Such is the rapid development and progress of information technology, which is one of the causes of changes in human life activities in various fields which have directly influenced the birth of new forms of legal action. For this reason, it is hoped that it is hoped that law enforcement officials should need to improve understanding and performance among law enforcement officers in preventing criminal acts of spreading suspected unlawful acts on social media and to the competent government it is necessary to increase resources and facilities and infrastructure in preventing acts that are illegal. can be detrimental to others due to social media. And for the public to be more careful and smarter in internet media, especially social media and it is not easy to spread information that is not yet clear, then people can become smart and wise internet users so that it does not cause problems in internet use